Pengaruh Motivasi, Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan PT Volta Indonesia Semesta Semarang - Sari, Ella Moonita; Moeljono, Moeljono (IJMA (Indonesian Journal of Management and Accounting), 2023)
This study aims to examine the effect of motivation, work environment and organizational culture on employee performance of PT Volta Indonesia Semesta Semarang. Some previous research on the influence of employee performance shows different results. Therefore, this study aims to review previous research on employee performance. This study used a sample of 80 employee respondents who were still working at PT Volta Indonesia Semesta Semarang. Data analysis techniques using multiple linear regression analysis, using the IBM SPSS Statistics 21.0 software program. The results indicate that the three variables, namely the work environment and organizational culture, do not have a positive and significant effect on employee performance. However, the motivation variable has a positive and significant effect on employee performance.